The Effect of the Old Fermentation of Liquid Organic Fertilizer with Rice Waste on Nitrogen Content, Phosphorus, and Potassium With the Addition of Human Urine - Fadhilah Achmad; Mariani H. Mansyur (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
One source of organic fertilizer that is abundantly available in the environment is urine from humans. Urine is believed to affect the quality of the soil as a plant growing media. In addition, fertilizers are processed from stale rice waste too widely used by farmers in increasing crop productivity. In general, this research was conducted to produce liquid organic fertilizer made from waste rice and human urine. In particular this research implemented to determine the length of fermentation of liquid organic fertilizer made from the best waste of rice and human urine based on chemical content analysis (nitrogen, phosphorus, and potassium) and look for the concentration of waste rice and urine humans are good for fertilization. The stage of this research methodology began by performing a liquid organic fertilizer formulation made from rice waste human urine is added and stored in a closed container for 4, 6, and 8 days then chemical analysis was carried out. The result show that the longer the fermentation of liquid organic fertilizer, the higher the content of N, P, and K produced. The 8-day fermentation time with a human urine concentration of 250 ml produced the best content with a nitrogen content of 3.17%, a phosphorus content of 2.68%, and a potassium content of 3.48%. Therefore, it is expected that the use of stale rice waste with the addition of human urine as a source of liquid organic fertilizer which is abundant in everyday life is easier to apply by the community and can contribute to entrepreneurship.